PENGARUH GAJI TERHADAP KINERJA GURU HONORER DI SMP NEGERI 2 SOLOKANJERUK KABUPATEN BANDUNG - Linda Noptalia; Karna Sopandi (JURNAL MITRA MANAJEMEN, 2023)
The aims of this study were (1) to find out the implementation of salary at SMP Negeri 2 Solokanjeruk, Bandung Regency (2) To find out the performance of honorary teachers at SMP Negeri 2 Solokanjeruk, Bandung Regency (3) to find out the effect of salary on the performance of honorary teachers at SMP Negeri 2 Solokanjeruk Regency Bandung. Furthermore, this type of research based on its method is ex post facto research which is part of the quantitative research method approach. The population in this study were all honorary teachers at SMP Negeri 2 Solokanjeruk, totaling 25 people and the data collection technique used was saturated sampling technique, which is a sampling technique when the entire population is used as a sample and is also known as a census. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis using simple regression. The results of the study can be concluded: 1) The salary as seen from the results of the assessment of 25 respondents is in the medium category, which is equal to 60%, 2) Honorary performance teachers as seen from the results of the assessment of 25 respondents are in the medium category, which is equal to 72%, 3) There is a significant influence between the variable salary on the performance of honorary teachers seen from the results of the assessment of 25 respondents from the results of inferential statistical analysis showed a value with a significant level of 5%. So the salary contribution to the performance of honorary teachers at SMP Negeri 2 Solokanjeruk has a significant effect through the calculation of tcount > ttable, namely 2.75 > 2,069 so that the variable X on Y has a positive and significant effect. Keywords: Salary, Performance